2004
DOI: 10.1002/dmrr.463
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of insulin content in the pancreas of female and male non‐obese diabetic mouse: implications for trials of diabetes prevention in humans

Abstract: We conclude that a reduction in pancreatic insulin content occurs slowly in the natural history of the disease and that such reduction only becomes apparent after diagnosis of hyperglycaemia. Occurrence of extensive lymphocytic infiltration in non-diabetic male mice is not accompanied by a reduction of insulin content in the pancreas. These findings have implications for designing studies in humans which aims to protect residual beta-cell function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…autoimmune disease in NOD mice. We confirmed that b cell death and leukocyte infiltration increased during diabetes progression in NOD mice aged 4-18 weeks (Figure 2a-c) as reported elsewhere [28,29]. Of note, treatment with the butanol fraction of B. pilosa inhibited b cell death and leukocyte infiltration in NOD mice aged from 4 to 18 weeks (Figure 2d-f).…”
Section: Resultssupporting
confidence: 91%
“…autoimmune disease in NOD mice. We confirmed that b cell death and leukocyte infiltration increased during diabetes progression in NOD mice aged 4-18 weeks (Figure 2a-c) as reported elsewhere [28,29]. Of note, treatment with the butanol fraction of B. pilosa inhibited b cell death and leukocyte infiltration in NOD mice aged from 4 to 18 weeks (Figure 2d-f).…”
Section: Resultssupporting
confidence: 91%
“…Although much has been learned about β-cell development and β-cell biology and function in vitro (using isolated pancreatic islets), studies designed to examine β-cell phenotype in vivo have suffered from technical limitations. For instance, currently available techniques to quantify pancreatic β-cell mass rely on laborious histomorphometric techniques ( 1 ) or on assumptions that β-cell mass correlates with β-cell function (stimulated C-peptide release) ( 2 ) or total pancreatic insulin content ( 3 , 4 ). Furthermore, quantifying the different endocrine islet cellular constituents by staining for the hormones produced (i.e., glucagon by α-cells, insulin by β-cells, somatostatin by δ-cells, and pancreatic polypeptide by PP-cells) has to date been challenging, relying again mostly on histomorphometry, and automated image processing setups typically allow only single-parameter analysis ( 5 , 6 ).…”
mentioning
confidence: 99%
“…Pancreatic insulin content was measured by extraction of frozen whole organ powder in acidic ethanol as described [32] . Pancreatic acid–ethanol extracts were centrifuged at 3000 g for 15 min at 4 °C and supernatants were collected.…”
Section: Methodsmentioning
confidence: 99%